Intersectionality and empathy in Afrofuturist feminist dystopian narratives: Octavia Butler’s Parable of the sower and Nalo Hopkinson’s Brown girl in the ring - Gartner, Lindsey (My University, 2021)
This article analyzes dystopian fiction’s representation, critique, and attempted rectification of oppressive social structures related to violence against women, black motherhood, and (dis)ability. The 1990s novels Parable of the Sower by Octavia Butler and Brown Girl in the Ring by Nalo Hopkinson represent what dystopian critics call “patriarchy on steroids.”. Drawing on feminist narrative theory and Afrofuturism theory, this article extends the scholarly discussion of feminist elements in both texts by analyzing representations of physical and sexual violence, which critics have largely overlooked, and the intersectional representation of black motherhood. Although Butler and Hopkinson depict violence against women and black motherhood in different ways and use different narrative techniques, both offer amplified reflections of the real-world intersectional and diverse experiences of women. Butler’s and Hopkinson’s young female protagonists challenge the societal oppressions and inequities they face through empathic reasoning: Butler’s Lauren reframes her embodied hyperempathy (dis)ability as a gift, enabling her to found an equitable community amidst violent social collapse, and Hopkinson’s Ti-Jeanne reframes her temporary zombification as an opportunity to empathize with other characters’ trauma, enabling her to defeat the violent gang leader Rudy. Lauren and Ti-Jeanne thereby imagine new positions for themselves and for women in general.
Keywords: dystopian fiction; violence against women; Afrofuturism; intersectional feminist theory